Cumulative drought and land‐use impacts on perennial vegetation across a North American dryland region. Issue 3 (11th February 2016) - Munson, Seth M.; Long, A. Lexine; Wallace, Cynthia S.A.; Webb, Robert H.
Abstract: Question: The decline and loss of perennial vegetation in dryland ecosystems due to global change pressures can alter ecosystem properties and initiate land degradation processes. We tracked changes of perennial vegetation using remote sensing to address the question of how prolonged drought and land‐use intensification have affected perennial vegetation cover across a desert region in the early 21st century? Location: Mojave Desert, southeastern California, southern Nevada, southwestern Utah and northwestern Arizona, USA. Methods: We coupled the Moderate‐Resolution Imaging Spectroradiometer Enhanced Vegetation Index (MODIS‐EVI) with ground‐based measurements of perennial vegetation cover taken in about 2000 and about 2010. Using the difference between these years, we determined perennial vegetation changes in the early 21st century and related these shifts to climate, soil and landscape properties, and patterns of land use. Results: We found a good fit between MODIS‐EVI and perennial vegetation cover (2000: R 2  = 0.83 and 2010: R 2  = 0.74). The southwestern, far southeastern and central Mojave Desert had large declines in perennial vegetation cover in the early 21st century, while the northeastern and southeastern portions of the desert had increases. These changes were explained by 10‐yr precipitation anomalies, particularly in the cool season and during extreme dry or wet years. Areas heavily impacted by visitor use or wildfire lost perennial vegetation cover, and vegetation in protected areas increased to a greater degree than in unprotected areas. Conclusions: We find that we can extrapolate previously documented declines of perennial plant cover to an entire desert, and demonstrate that prolonged water shortages coupled with land‐use intensification create identifiable patterns of vegetation change in dryland regions. Abstract : The decline of perennial vegetation in drylands can initiate land degradation. Munson et al. (this issue) used remote sensing to determine decadal changes of perennial vegetation across the Mojave Desert, USA in the early 21st century. They highlight how prolonged drought, soil properties, wildfire, visitor use, and protected area status have broadly affected perennial vegetation cover.